Association of changes in work shifts and shift intensity with change in fatigue and disturbed sleep: a within-subject study - Härmä, Mikko; Karhula, Kati; Ropponen, Annina; Puttonen, Sampsa; Koskinen, Aki; Ojajärvi, Anneli; Hakola, Tarja; Pentti, Jaana; Oksanen, Tuula; Vahtera, Jussi; Kivimäki, Mika (Scandinavian Journal of Work, Environment ＆ Health, 2018)
Objectives: The aim of this study was to examine whether changes in work shifts and shift intensity are related to changes in difficulties to fall asleep, fatigue, and sleep length. Methods: Questionnaire responses of hospital employees (N=7727, 93% women) in 2008, 2012, 2014 and 2015 were linked to daily-based records of working hours during three months preceding each survey. We used conditional logistic regression and longitudinal fixed-effects analyses to investigate odds ratios (OR) and 95% confidence intervals (CI) for each 25% within-individual change in the proportion of working hour characteristics in relation to changes in fatigue, difficulties to fall asleep, and 24-hour sleep length. Results: Change in night but not in morning or evening shifts was associated with parallel changes in odds for longer sleep length (OR 1.45, 95% CI 1.28-1.64) and fatigue during free days (OR 1.38, 95% CI 1.16-1.64). Similarly, short shift intervals and having ＞2 but not ＞4 consecutive night shifts were associated with increased odds of fatigue during work and difficulties to fall asleep (OR 1.42, 95% CI 1.19-1.72 and OR 1.10, 95% CI 1.05-1.19, respectively). Among workers aged ≥50 years, the associations were the strongest between night shifts and longer sleep (OR 2.24, 95% CI 1.52-3.81) and between higher proportion of short shift intervals and fatigue during free days (OR 1.68, 95% CI 1.10-2.54). Conclusions: Among shift workers with fatigue or sleep problems, decreasing the proportion of night shifts and quick returns and giving preference to quickly forward-rotating shift systems may reduce fatigue.